Ultramorphology and histology of dorsal vessel - Gastral portion - Of Camponotus rufipes - Marques, Renato Matos [UNESP]; Caetano, Flávio Henrique [UNESP] (My University, 2001)
The dorsal diaphragm of Camponotus rufipes (Hymenoptera: Formicidae) is a thin membrane structure, with free edges between the points of attachment to the body wall that almost cover the whole extension of the dorsal vessel at its abdominal portion. A layer of fat body cells covers the region of the cuticle above the dorsal vessel and the incurrent ostia can be a vertical or horizontal slit in the wall of the heart. One organized structure as a network ofalary muscles was observed holding the heart at its middorsal position and supporting the pericardial cells too. A great number of pericardial cells were found laterally associated with the heart and cellular projections from those cells insert directly into the heart wall.
Keywords: Ants; Camponotus; Dorsal vessel; Histology; Ultramorphology